Expatriates, subsidiary autonomy and the overseas subsidiary performance of MNEs from an emerging economy - Tao, Fang; Liu, Xiaohui; Gao, Lan; Xia, Enjun (International journal of human resource management, 2018)
Despite a growing body of research on the role of expatriates in subsidiary performance, the mechanisms through which expatriates affect subsidiary performance are still the subject of debate. Drawing on resource dependence theory, we examine the indirect effects of expatriates on subsidiary performance via subsidiary autonomy based on a sample of Chinese multinational enterprises. The findings show that an increase in expatriates reduces the level of subsidiary autonomy and thus negatively affects subsidiary performance. We also find that the institutional quality of host countries reinforces the negative impact of expatriates on subsidiary autonomy, but reduces the importance of the latter on subsidiary performance.